Long non-coding RNAs in cancer progression - Tano, Keiko; Akimitsu, Nobuyoshi (Frontiers in Genetics, 2012)
Recent large-scale transcriptome analyses have revealed that transcription is spread throughout the mammalian genomes, yielding large numbers of transcripts, including long non-coding (lnc) RNAs with little or no protein-coding capacity. Dozens of lncRNAs have been identified as biologically significant. In many cases, lncRNAs act as key molecules in the regulation of processes such as chromatin remodeling, transcription and post-transcriptional processing. Several lncRNAs (e.g., MALAT1, HOTAIR and ANRIL) are associated with human diseases, including cancer. Those lncRNAs associated with cancer are often aberrantly expressed. Although the underlying molecular mechanisms by which lncRNAs regulate cancer development are unclear, recent studies have revealed that such aberrant expression of lncRNAs affects the progression of cancers. In this review, we highlight recent findings regarding the roles of lncRNAs in cancer biology.